Youth participation strategies in sustainable development goals implementation in Malaysia and Indonesia / Mohd Idham Mohd Yusof ... [et.al.]. - Mohd Yusof, Mohd Idham; Harsono, Dwi; Tuan Ismail, Tuan Nooriani; Abd Rahman, Farah Adilla (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Youths are considered integral stakeholders in implementing Sustainable Development Goals (SDGs), which will conclude in 2030. Their participation will determine the success of the global development agenda which has been promoted by the United Nations (UN) since 2015. This study reviewed 33 Scopus-indexed journal articles contributing to the discussion on youth participation in sustainable development or SDG-related programmes in Malaysia and Indonesia. The findings revealed that most journals implicitly placed SDGs as the central discussion theme. Nevertheless, reviewed journals were eligible for inclusion in the study as the articles focused on three sustainability pillars (environmental, social and economic dimensions). The results revealed that youth participation strategies for sustainable development or SDG-related programmes occurred at the school and university levels.